Analysis Systematic Literature Review: The Study of HRM Transformation Into Digital-Based GHRM Future Research Agenda - Puspa Dewi Yulianty; Syamsul Hadi Senen (West Science Business and Management, 2023)
Eco-friendly human resources can help sustainable business continuity. The current research aims to propose a business model theoretical framework that adapts to the new environment, addresses sustainable goals and gaps in the field, and builds a resilient and agile system for the business ecosystem. To approach the research problem, this study used the R-based Bibliometrix tool. The Scopus database selected and analyzed papers as part of five research steps. Bibliometric tools such as Biblioshiny, VOSviewer, and R Studio have been used to illustrate the findings. This study’s findings highlight several factors that will form the foundation of the proposed model. Green competencies, both natural and acquired, and the requirement to provide green motivation, were identified as important for developing the new business model.